SCIENTIFIC TECHNOLOGY PARKS - Miroslav Milutinović; Milica Radović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The overall objective of the development of industrial companies in the Technology park is the introduction of economically profitable production with efficient use of renevvable resources and use of highest environmental standards. Realization of the basic development goal of the Technology Park includes: creating a favorable business atmosphere in the local environment, attractive for foreign and domestic investors, supporting the establishment of small and medium enterprises using different models of joint ventures and foreign direct investments